The Influence of Environmental Cues on the Development of Trypanosoma cruzi in Triatominae Vector - Melo, Raíssa de Fátima Pimentel; Guarneri, Alessandra Aparecida; Silber, Ariel Mariano (Frontiers in Cellular and Infection Microbiology, 2020)
Trypanosoma cruzi, a hemoflagellate parasite, is the etiological agent of Chagas disease that affects about 6 to 7 million people worldwide, mostly in Latin America. The parasite life cycle is complex and alternates between an invertebrate host - Triatominae vector - and a mammalian host. The parasite adaptation to the several microenvironments through which it transits is critical to success in establishing infection. Moreover, environmental cues also play an important role on the parasite development and it can modulate the infection. In the present study, we discussed how the temperature oscillations and the nutritional state of the invertebrate host can affect the parasite development, multiplication and the differentiation process of epimastigote forms into metacyclic trypomastigotes, called metacyclogenesis. The impact of oxidative imbalance and osmotic stresses on the parasite-vector relationship are also discussed.